Biocompatibility and Therapeutic Effect of 3 Intra-Tympanic Drug Delivery Vehicles in Acute Acoustic Trauma - Park, Mina; Hwang, Yu Jung; Noh, Tae Soo; Woo, Shin Wook; Park, Ji Hoon; Park, Seung Hun; Kim, Moon Suk; Suh, Myung Whan (Audiology and Neurotology, 2020)
Introduction: The aim of this study was to assess the biocompatibility of several intra-tympanic (IT) drug delivery vehicles and to compare hearing outcomes. Materials and Methods: After acute acoustic trauma, rats were treated with IT 10 mg/mL dexamethasone phosphate (D) and divided into the following groups for drug delivery: saline + D (n = 15), hyaluronic acid (HA) + D (n = 17), and methoxy polyethylene glycol-b-polycaprolactone block copolymer (MP) + D (n = 24). Results: No inflammation was found in the saline + D or HA + D groups. The duration of vehicle/drug persistence in the bulla was significantly longer for the MP + D (47.5 days) and HA + D groups (1.8 days) than for the saline + D group (<1 day). The tympanic membrane was significantly thicker in the MP + D group than in the saline + D and HA + D groups. The proportion of ears with good hearing outcome was significantly higher (63.6%) in the HA + D group than in the MP + D group. The number of hair cells in the hearing loss (HL) control group was significantly lower than in the MP + D group. Discussion/Conclusion: HA shows great potential as a biocompatible vehicle for D delivery via the IT route, without an inflammatory reaction and with better hearing outcomes. Considering inflammation and hearing, MP may not be a good candidate for IT drug delivery.
Keywords: Animals; Dexamethasone; Evoked Potentials, Auditory, Brain Stem; Glucocorticoids; Hearing; Hearing Loss, Noise-Induced; Injection, Intratympanic; Male; Rats; Rats, Sprague-Dawley; Treatment Outcome; Tympanic Membrane; Acoustic trauma; Auditory brainstem-evoked responses; Drug delivery; Hearing loss; Inner ear